THE EFFECTIVENESS OF THE IMPLEMENTATION OF HYPNOTEACHING METHOD TO IMPROVE MOTIVATION AND MATHEMATICS LEARNING RESULT OF CLASS VII STUDENTS AT SMPN 41 BULUKUMBA - Kasmaja DS, Hadi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
This study is an pre-experiment research which aims at examining (1) the implementation result of hypnoteaching method in Mathematics learning of class VII students at SMPN 41 Bulukumba, (2) the learning motivation of class VII students at SMPN 41 Bulukumba before and after being taught using hypnoteaching method, and (3) the extend of improvement of students’ learning result of class VII at SMPN 41 Bulukumba taught by using hypnoteaching method. The population of the study was all class VII students at SMPN 41 Bulukumba. The sample was class VIIb students at SMPN 41 Bulukumba. The sample was class VIIb students’ learning result on learning using hypnoteaching method. Based on the effectiveness level criteria, the hypnoteaching method learning was adequately effective to be implemented on rectangular subject. It was proved by the students’ learning result of class VII at SMPN 41 Bulukumba before implementing hypnoteaching method which achieved the mean score 40.24 and was in incomplete category; whereas after being taught by using hypnoteaching method, it achieved the mean score 76.59 that approximately 75% students had fulfilled minimal completeness criteria so it achieved classical completeness with fair category. The result of the study showed that the implementation of learning using hypnoteaching method for six sessions was in the category of completely implemented with the mean score 3.6. There was improvement of learning motivation of students after being taught by using hypnoteaching method from the mean score 95.96 improved to 112. There was improvement of Mathematics learning result of students in class VII at SMPN 41 Bulukumba after being taungt by using hypnoteaching method with the improvement of students’ learning result counted using normalized gain formula by 0.61